Penatalaksanaan Holistik Pasien Laki-laki Usia 35 Tahun dengan Dermatitis Atopik Melalui Pendekatan Kedokteran Keluarga - Arba Indra Putra; dian isti anggraini (Medula, 2022)
Atopic Dermatitis (hereinafter referred to as AD) is a typical, chronic, and frequent relapse (exacerbation) inflammatory skin disease which, although rare, can be found in adult patients. Atopic dermatitis found in adults is more caused by psychological stress and is supported by decreased function of the autonomic nervous system. This article is a form of the application of family doctor services based on evidence based medicine to patients by identifying risk factors, clinical problems, and patient management based on the framework of solving patient problems with a patient centered and family approach. This study is a Case Report. Primary data were obtained through autoanamnesis, physical examination, home visits to complete family and psychosocial data, as well as the environment. Assessment based on a holistic diagnosis from the beginning, process and end of the study quantitatively and qualitatively. Adult patient with atopic dermatitis. On internal factors in the case such as genetic factors, age, and ignorance of the precipitating factor. External factors are the lack of family knowledge about atopic dermatitis, its complications and the environment that has many allergens. Pharmacological and non-pharmacological interventions were carried out in the form of education in preventing the recurrence of atopic dermatitis symptoms in patients. Enforcement of diagnosis and management of these patients has been carried out holistically, patient centered, family approach and based on several theories and the latest research. In the process of behavior change, patients and families have reached the adoption stage.